A Naturally Occurring Flavone (Chrysin): Chemistry, Occurrence, Pharmacokinetic, Toxicity, Molecular Targets and Medicinal Properties. Issue 4 (4th July 2018) - Siddiqui, Amir; , Badruddeen; Akhtar, Juber; Uddin M.S., Shahab; Khan, Mohammad Irfan; Khalid, Mohammad; Ahmad, Mohammad
Abstract: Naturally occurring flavonoids are directly associated with human dietary ingredients and health, there is need to evaluate the impact of commonly consumed flavonoids, on human health and diseases. Flavonoids possess number of beneficial effects along with mitigation of diseases both in-vitro as well as in-vivo experimental conditions. Chrysin, a naturally occurring flavones most abundantly found in numerous plant including fruits and vegetables, possesses potent anti-diabetic, anti-inflammatory in addition to antioxidant activities. Chrysin acts on various molecular targets and modulate different signaling pathways of inflammation (NFkB, PXR, TBK1) and cellular metabolism (AMPK/AKT/ERK/PPAR). Furthermore, positive effects of chrysin on browning of fat and obesity also have been reported. The present review highlights the chemistry, sources, pharmacokinetic, molecular targets and toxicity of chrysin as well as its pharmacological potential.